2004
DOI: 10.1016/j.ydbio.2004.01.004
|View full text |Cite
|
Sign up to set email alerts
|

FGF8 dose-dependent regulation of embryonic submandibular salivary gland morphogenesis

Abstract: FGF8 has been shown to play important morphoregulatory roles during embryonic development. The observation that craniofacial, cardiovascular, pharyngeal, and neural phenotypes vary with Fgf8 gene dosage suggests that FGF8 signaling induces differences in downstream responses in a dose-dependent manner. In this study, we investigated if FGF8 plays a dose-dependent regulatory role during embryonic submandibular salivary gland (SMG) morphogenesis. We evaluated SMG phenotypes of Fgf8 hypomorphic mice, which have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 57 publications
4
78
0
1
Order By: Relevance
“…Although the function of Shh in SMG morphogenesis is not entirely clear, Fgf8, a potent mitogen that is essential for the growth of SMG (Jaskoll et al, 2004b), has been proposed to act downstream of Shh, as exogenous Fgf8 was shown to rescue the growth defect of cyclopamine-treated SMGs (Jaskoll et al, 2004a). In line with this, qRT-PCR analysis of Eda-null SMGs at later stages (E16 to newborn) indicated that both Shh and Fgf8 were downregulated (Melnick et al, 2009).…”
Section: Discussionmentioning
confidence: 90%
“…Although the function of Shh in SMG morphogenesis is not entirely clear, Fgf8, a potent mitogen that is essential for the growth of SMG (Jaskoll et al, 2004b), has been proposed to act downstream of Shh, as exogenous Fgf8 was shown to rescue the growth defect of cyclopamine-treated SMGs (Jaskoll et al, 2004a). In line with this, qRT-PCR analysis of Eda-null SMGs at later stages (E16 to newborn) indicated that both Shh and Fgf8 were downregulated (Melnick et al, 2009).…”
Section: Discussionmentioning
confidence: 90%
“…Targeted overexpression of FGF7 with the K14 promoter caused smaller salivary glands, excessive salivation, and a delay in gland differentiation (Guo et al, 1993). FGF8-conditional mutant and FGF8-hypomorphic mice also have defects in SMG development and differentiation (Jaskoll et al, 2004). Taken together, these studies suggest a primary role for FGF10/FGFR2b signaling in the initiation of the gland, an essential role for FGF8 at later stages, and possibly a role for FGF7 during differentiation.…”
Section: Introductionmentioning
confidence: 86%
“…The specification of appendage type may then be effected at least in part by variations in the Shh pathway (see below). In contrast to hair follicles and sweat glands, salivary gland early stage development depends instead on Fgf and Pitx2 pathways (Jaskoll et al, 2004b;Tucker, 2007). Eda and Shh pathways are then required for latestage branching morphogenesis (Häärä et al, 2011;Patel et al, 2011).…”
Section: Various Appendages Display Distinctive Signaling Interactionmentioning
confidence: 99%